Performing control in the Swedish Twitter sphere or: How a 1920s' Russian linguist helps us understand dynamics of digital authority - Turunen, Jaakko; Werther, Steffen; Al-Saqaf, Walid (Frontiers in Political Science, 2022)
Social media has created new public spheres that provide alternative sources of social and political authority. Such “digital authority” has conventionally been interpreted in metric terms, without qualitative distinctions. Based on Twitter data from four different Swedish state agencies during the first 15 months of the Covid-19 crisis, this paper looks at the different kinds of modes of interaction Twitter enables and their impact on state agencies digital authority. Theoretically this paper applies Valentin Voloshinov’s classical theory on reported speech, developed in the 1920s, to the concept of digital authority in the Twitter-sphere of the 2020s. Besides these theoretical contributions to media and communication studies, the main findings are that retweets are generally used to affirm and spread information thus strengthening the digital authority of the origin of the tweet whilst replies and quote-tweets are used to undermine the credibility of the sender and the content of the original tweet, often by resorting to irony. As the Covid-19 crisis prolongs, we observe increasing share of critical commentary and diminishing overall attention to government actors in Sweden. The roles of different state agencies are mirrored by the type of interaction they generate. This article also shows the usefulness of qualitative study of social media interaction in order to reveal the dynamics of digital authority construed in social media.